The Impact of Self-Efficacy on Career Choices of Generation Z: The Mediating Role of Decision-Making Difficulties in DKI Jakarta - Basid, Rezqi Ananda; Nisya, Dela Ainun (Jurnal Manajemen Bisnis, 2024)
The Generation Z population is the largest demographic group in Indonesia currently entering the workforce. However, data from the Central Statistics Agency (BPS) indicates that youth unemployment remains a critical issue in the employment sector. The increasing open unemployment rate among Generation Z can be attributed to an imbalance between labor demand and supply, as well as career decision-making processes during school or university periods. This study aims to analyze the factors influencing OUR among Generation Z, specifically through the career decision-making process before entering the workforce. Furthermore, this research examines the influence of Self-Efficacy in Career Decision-Making on Career Decisions through the mediating variable of Career Decision-Making Difficulties. The methodology employed is a survey, with data collected via questionnaires distributed to 104 respondents who meet the study criteria. The instruments used include the Career Decision Scale (CDS), the short-form Career Decision-Making Self-Efficacy (CDMSE-SF), and the Career Decision-Making Difficulties Questionnaire (CDDQ). The findings reveal an indirect influence of Self-Efficacy in Career Decision-Making on Career Decisions, mediated by Career Decision-Making Difficulties among Generation Z individuals entering the workforce in DKI Jakarta.